Water distribution model for center pivot end gun sprinklers - Giuliani Prado; Alberto Colombo; Antônio C. Barreto (Revista Brasileira de Engenharia Agrícola e Ambiental)
ABSTRACT End gun sprinklers can increase the irrigated area by center pivot irrigation systems without a substantial investment. This study was carried out at the Universidade Federal de Lavras, MG state, Brazil, and aimed to describe and validate a water distribution model for center pivot end gun sprinklers. The gun sprinkler PLONA-RL250®, attached at the end point of a center pivot, was used to evaluate the model in field tests. The sprinkler working conditions considered were nozzle diameters of 14 x 6 mm, working pressure of 292 kPa, and four asymmetric wetted angle adjustments (95 + 20º; 90 + 90º; 60 + 60º; 45 + 45º). These tests were carried out for wind speed lower than 0.9 m s-1. The measured and simulated irrigation depths showed an average absolute difference of 0.65 mm and determination coefficients from 71.55 to 89.37%. Based on the confidence coefficient (c = 0.82) the model can be classified as very good (0.76 ≤ c ≤ 0.85). Sprinkler wetted angle adjustment of 110º (95 + 20º) resulted in uniform water distribution and, for effective radius of throw between 70 to 90% of the gun sprinkler´s radius of throw, this working condition resulted in Christiansen’s uniformity greater than 80%.